Pengaruh Pembelajaran Dalam Jaringan Dengan Aplikasi Google Classroom Terhadap Minat Belajar Siswa Di Smp Plus Muda Prakarya - edy; M. Farhan Wahid; Zaenal Abidin (Khidmatussifa: Journal of Islamic Studies, 2022)
The method used is a quantitative method. This method is used to determine whether there is an effect of online learning with the Google Classroom application on students' interest in learning at SMP Plus Muda Prakarya. The research instrument used to obtain data is by using product moment correlation analysis. The variable studied in this study is the effect of Online Learning (X) on Students' Interest in Learning (Y). Based on the product moment analysis, the value of "r" count = 0.299. By examining the table for the value of "r" product moment, it turns out that for dk = N-2 = 28-2 = 26 at a significant level of 5%, we get "r" table = 0.388 and at a significant level of 1%, we get "r' table = 0.496. Then it can be concluded that "r" count = 0.299 < "r" table = 0.496. In accordance with the provisions of "if "r" count is smaller than "r" table, then Ho is accepted and Ha is rejected. But on the other hand, if the "r" count is greater than the "r" table, then Ha is accepted and Ho is rejected". Thus, it means that there is no significant effect between online learning on student interest in learning at SMP Plus Muda Prakarya. Then by paying attention to the "r" count = 0.299 in the interpretation table the data is between 0.20 - 0.399 which means that there is no correlation between X and Y variables, even "Low". From the calculation of KD (Coefficient of Determination) it can be concluded that the influence between Variable X (Learning Online) and Variable Y (Students' Interest in Learning) only reaches 8.29%. Thus, there are other factors that affect student learning interest, which is 91.71%. Based on the results of the analysis above through this research, it can be concluded that there is no real influence between online learning on the learning interest of students in SMP Plus Muda Prakarya. Keywords: Online Learning, Students' Interest in Learning